2012
DOI: 10.3113/fai.2012.0722
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Corticosteroid Injection versus Size of Plantar Interdigital Neuroma

Abstract: A single ultrasound-guided corticosteroid injection resulted in generally short-term pain relief for symptomatic Morton's neuromas. The effectiveness of the injection appears to be more significant and long-lasting for lesions smaller than 5 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 18 publications
3
25
0
1
Order By: Relevance
“…We found that as the size of the neuroma increased, the probability of needing further intervention within 2 years increased. This corresponds with the findings of Makki et al [9], where patients with neuromas larger than 5 mm had overall worse pain scores by six months post injection compared to neuromas less than 5 mm. In their study however, the neuromas were measured in the sagittal plane using ultrasonography whereas our radiologists recorded the largest diameter measurable in either the sagittal or coronal planes.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We found that as the size of the neuroma increased, the probability of needing further intervention within 2 years increased. This corresponds with the findings of Makki et al [9], where patients with neuromas larger than 5 mm had overall worse pain scores by six months post injection compared to neuromas less than 5 mm. In their study however, the neuromas were measured in the sagittal plane using ultrasonography whereas our radiologists recorded the largest diameter measurable in either the sagittal or coronal planes.…”
Section: Discussionsupporting
confidence: 89%
“…Twenty nine feet (51%) received further treatment in the form of one additional corticosteroid injection (11 cases, 19%) and surgical excision (18 cases, 32%). Patients who did not receive further treatment had significantly smaller neuromas (median of 8 mm [7][8][9][10][11][12] versus 10 mm [8.5-14.5]) and were older (mean of 59.4 AE 9.3 years versus 51.6 AE 12.4 years) ( Table 1).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The initial treatment of metarsalgia is mainly conservative [1][2][3]18] and includes the use of pads and orthopedic shoes, rehabilitation, and steroid and anesthetic injections [27,[29][30][31]. Makki et al [32] concluded that a single ultrasound-guided corticosteroid injection results in generally short-term pain relief for symptomatic Morton's neuromas. The effectiveness of the injection appears to be more significant and long-lasting for lesions smaller than 5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have shown that ultrasound-guided steroid injections are both effective and cost effective for short-term pain relief usually at 3 months, with the effect ranging between 4 weeks and 9 months and being more significant and long lasting if the injection is delivered early in the course of symptoms and for lesions ,5 mm. [75][76][77][78][79] Ultrasound-guided alcohol injections are an alternative effective treatment. Partial or total pain relief has been reported in up to 94% of patients at 6 months and in 74% of patients at 1 year after the injection, with 30% ultrasound-proven reduction in lesion size at 6 months.…”
Section: Morton's Neuromamentioning
confidence: 99%